Pengaruh Model Discovery Learning Berbantuan Komik Digital Flip Book dalam Upaya Meningkatkan Hasil Belajar IPS di Sekolah Dasar - Anggraeni, Windy; Wahyudin, D; Mulyani, Srie (FONDATIA, 2023)
This research is motivated by the learning process which demands active participation from the learner, but in reality the learning process still tends to reduce the role and participation of students. This study intends to see how much influence the digital comic-assisted discovery learning model flip book has in efforts to improve social studies learning outcomes for fifth grade students in the 2022/2023 academic year to find out whether the digital comic-assisted discovery learning model is more effective than the digital flip book learning model. conventional. This study used a quasi-experimental method with a nonequivalent control group pre-test and post-test design. This research was conducted at SDN 1 Cibening with 25 students in class VA and 24 students in class VB as research samples. The instrument used in this study is a test. Based on the research findings, it shows that the discovery learning model assisted by digital flip book comics has an effect on student learning outcomes with an effect of 79.4%. The discovery learning model assisted by digital flip book comics is more effective than the conventional learning model with the difference in the pretest and posttest average scores, in the experimental class being greater than the control class. Overall, the increase in student learning outcomes in the experimental class belongs to the quite effective category, while the control class belongs to the less effective category. From the results of this study, it can be concluded that the comic digital flip book-assisted discovery learning model has an effect on efforts to improve social studies learning outcomes for fifth grade students in elementary schools and the digital flip book-assisted discovery learning model is more effective.